The Association Between Asphyxia and Neonatal Pathological Jaundice Incidence in Umbu Rara Meha Hospital East Sumba Regency - Hartati Liawat, Fitri; Andriyanti, Andriyanti; Utomo, Budi (PT. Publikasiku Academic Solution, 2024)
Jaundice causes 70% morbidity and 10% infant mortality worldwide, approximately 1.1 million newborns are affected by jaundice every year. The purpose of this study was to analysis the association between asphyxia and the incidence of neonatal pathological jaundice at Umbu Rara Meha Hospital, East Sumba Regency. The research used a quantitative method with case and control approach using secondary collection data medical records from January to October 2023. The sample ratio was 1:1, the case group sample is 75 babies with jaundice and the control group sample is 75 babies who were born in the hospital. The sampling taken by consecutive sampling. The analysis used the Chi-square test. The data analysis showed there was an association between asphyxia and neonatal pathological jaundice incidence with p=0.001. The data result showed there was an association between asphyxia and neonatal pathological jaundice incidence at Umbu Rara Meha Hospital, East Sumba Regency.